Aqueous transfer of colloidal metal oxide nanocrystals via base-driven ligand exchange. Issue 68 (3rd August 2022) - Lakhanpal, Vikram S.; Zydlewski, Benjamin Z.; Gan, Xing Yee; Celio, Hugo; Jhong, Huei-Ru "Molly"; Ofosu, Charles K.; Milliron, Delia J.
Abstract : In our work we develop a base-driven ligand stripping method for metal oxide nanocrystals, replacing oleate ligands with hydroxyls to create an aqueous dispersion. We generalize this method across a range of material compositions, particle sizes, and particle shapes to get stable dispersions. Abstract : A general method is developed for removal of native nonpolar oleate ligands from colloidal metal oxide nanocrystals of varying morphologies and compositions. Ligand stripping occurs by phase transfer into potassium hydroxide solution, yielding stable aqueous dispersions with little nanocrystal aggregation and without significant changes to the nanomaterials' physical or chemical properties. This method enables facile fabrication of conductive films of ligand-free nanocrystals.